2018
DOI: 10.1080/2162402x.2018.1424676
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial ghosts as adjuvant to oxaliplatin chemotherapy in colorectal carcinomatosis

Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed cancers and a major cause of cancer mortality worldwide. At late stage of the disease CRC often shows (multiple) metastatic lesions in the peritoneal cavity which cannot be efficiently targeted by systemic chemotherapy. This is one major factor contributing to poor prognosis. Oxaliplatin is one of the most commonly used systemic treatment options for advanced CRC. However, drug resistanceoften due to insufficient drug deliveryis still hampering succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 85 publications
0
26
1
Order By: Relevance
“…Interestingly, OXA alone could promote the release of ATP and HMGB1, two hallmarks of ICD, that were not mandatory for the immunizing capacities of dying IEC, in contrast to live bacteria or pathogen associated molecular patterns (26). This is in contrast with a report utilizing gram negative bacteria ghosts injected intraperitoneally with OXA that could turn on ICD in the peritoneal cavity and elicit potent NKT and CD8 + T cell responses associated with regression of peritoneal carcinogenesis (247). These observations emphasize that the tumor macroenvironment and organ may critically influence the requirements for efficient priming of a T cell response.…”
Section: Towards a Solution To The Paradox Of Colon Cancersmentioning
confidence: 70%
“…Interestingly, OXA alone could promote the release of ATP and HMGB1, two hallmarks of ICD, that were not mandatory for the immunizing capacities of dying IEC, in contrast to live bacteria or pathogen associated molecular patterns (26). This is in contrast with a report utilizing gram negative bacteria ghosts injected intraperitoneally with OXA that could turn on ICD in the peritoneal cavity and elicit potent NKT and CD8 + T cell responses associated with regression of peritoneal carcinogenesis (247). These observations emphasize that the tumor macroenvironment and organ may critically influence the requirements for efficient priming of a T cell response.…”
Section: Towards a Solution To The Paradox Of Colon Cancersmentioning
confidence: 70%
“…empty envelopes of Gram-negative bacteria) with oxaliplatin to elicit therapeutically relevant T cell responses against CT26 mouse colorectal tumors coupled to the establishment of long-term immunological memory. 363 Gao and collaborators (University of Science and Technology of China, Hefei, China) found that, as compared to the either agent delivered as standalone therapy, the co-administration of doxorubicin and a small molecule IDO1 inhibitor (NLG919) profoundly inhibits the growth of 4T1 mouse mammary tumors in vivo. 364 Gebremeskel and colleagues (Beatrice Hunter Cancer Research Institute, Halifax, Nova Scotia, Canada) combined cyclophosphamide, gemcitabine and α-galactosylceramide (α-GalCer)-loaded DCs (which potently activate NKT cells), achieving disease eradication and long-term immunological protection in mice bearing 4T1 tumors, as demonstrated by their ability to reject a subsequent challenge with the same cancer cells.…”
Section: Recent Preclinical Advancesmentioning
confidence: 99%
“…Its use within a systemically applied, targeted gene delivery system would be the next logical step, where specificity of delivery (e.g., using cell-targeting ligands) and/or specificity of expression (using tumor-specific promoters or miRNA-based de-targeting approaches) is further pursued. 16 , 18 , 45 For preclinical studies, syngeneic tumor models need to be evaluated (e.g., CT26 colon cancer in BALB/c mice 14 , 46 ). This is important as the adaptive immune system, especially CD8+ cytotoxic T cells, is also involved in tumor eradication after CD47 blockage.…”
Section: Discussionmentioning
confidence: 99%